2017
DOI: 10.1103/physreva.96.031801
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin semiconductors as nonlinear mirrors

Abstract: We show that a transition metal dichalcogenide monolayer with a radiatively broadened exciton resonance would exhibit perfect extinction of a transmitted field. This result holds for s-or p-polarized weak resonant light fields at any incidence angle, due to the conservation of in-plane momentum of excitons and photons in a flat defect-free two dimensional crystal. In contrast to extinction experiments with single quantum emitters, exciton-exciton interactions lead to an enhancement of reflection with increasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…S6 [18] shows that the extinction remains unchanged as we vary the incident intensity by 4 orders of magnitude from 0.5 to 400 W=cm 2 . Verification of the theoretically predicted unusual saturation characteristics of TMD mirrors is likely to require pulsed laser excitation [13].…”
Section: (C)mentioning
confidence: 99%
See 2 more Smart Citations
“…S6 [18] shows that the extinction remains unchanged as we vary the incident intensity by 4 orders of magnitude from 0.5 to 400 W=cm 2 . Verification of the theoretically predicted unusual saturation characteristics of TMD mirrors is likely to require pulsed laser excitation [13].…”
Section: (C)mentioning
confidence: 99%
“…These narrow linewidths have a dominant contribution from radiative decay of ∼1.5 meV for MoSe 2 [11,12]. Motivated by these developments, we previously analyzed the optical response of a monolayer TMD theoretically [13] and showed that it realizes an atomically thin mirror [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their miniaturization is fundamentally limited by the optical wavelength in the case of dielectric mirrors and photonic crystals (1) or by the skin depth for metallic mirrors (2). Recently, resonant scattering has emerged as a method for overcoming these limitations and for controlling light at the atomic scale (3)(4)(5)(6)(7)(8)(9)(10)(11). For instance, highly reflective mirrors based on individual quantum emitters have been demonstrated by coupling them to optical cavities and nanophotonic waveguides (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Such resonant mirrors feature very unusual properties due to their extraordinary nonlinearity down to the single-photon level (3)(4)(5)(6)(7)(8). A two-dimensional (2D) layer of emitters, such as atomic lattices or excitons (9)(10)(11), has also been predicted to act as an efficient mirror when the incident light is resonant with the resonance frequency of the system. Such atomically thin mirrors represent the ultimate miniaturization limit of a reflective surface, and could enable unique applications ranging from quantum nonlinear optics (9-11) to topological photonics (12,13).…”
mentioning
confidence: 99%